EVALUACION DE DIFERENTES DENSIDADES DE LA MICROALGA NANNOCHLOROPSIS OCULATA COMO ALIMENTO PARA ARTEMIA (Boletín de Investigaciones Marinas y Costeras, 2016)
Laboratory experiments were carried out to determine the possibility of using the microalgae Nannochloropsis oculata as a food source for brine shirmp. Among the range concentrations studied (3 x 105 to 14 x 105 cells/ml), 12 x 105 cells/ml offered the best results of survival and growth rate and it is recommended as the most effective. From correlation matrix, high values (r > 0.90; a = 0.05) were obtained for the relation of microalgae concentration and survival, growth rate and the variation of average lenght. The minimum cellular concentration of microalgae which is necessary for brine shrimp culture is 5.6 x 105 cells/ml.